2011
DOI: 10.3402/polar.v30i0.5971
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal variability of polynya dynamics and ice production in the Laptev Sea between the winters of 1979/80 and 2007/08

Abstract: Polynyas in the Laptev Sea are examined with respect to recurrence and interannual wintertime ice production. We use a polynya classification method based on passive microwave satellite data to derive daily polynya area from long-term sea-ice concentrations. This provides insight into the spatial and temporal variability of open-water and thin-ice regions on the Laptev Sea Shelf. Using thermal infrared satellite data to derive an empirical thin-ice distribution within the thickness range from 0 to 20 cm, we ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
143
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(164 citation statements)
references
References 25 publications
14
143
4
Order By: Relevance
“…The model is derived from the data overlapping period (2002)(2003)(2004)(2005)(2006)(2007)(2008). A detailed description of the methodology is given in Willmes et al (2011). The comparison of ice area flux in late winter/early spring with summer ice anomalies of the following summer reveals a negative coupling that support our assumption (Fig.…”
Section: Linkage Between Ice Area Flux and Summer Ice Conditionssupporting
confidence: 78%
See 2 more Smart Citations
“…The model is derived from the data overlapping period (2002)(2003)(2004)(2005)(2006)(2007)(2008). A detailed description of the methodology is given in Willmes et al (2011). The comparison of ice area flux in late winter/early spring with summer ice anomalies of the following summer reveals a negative coupling that support our assumption (Fig.…”
Section: Linkage Between Ice Area Flux and Summer Ice Conditionssupporting
confidence: 78%
“…In the following, we will focus on the potential linkage that exists between presence/absence of extensive thin ice areas in late winter and the occurrence of low/high summer ice extent. Thin ice areas can be derived directly from AMSR-E and SSM/I scenes, using the Polynya Signature Simulation Method (PSSM, Markus and Burns, 1995;Kern, 2009;Willmes et al, 2011). The method provides a classification of thin ice and open water (polynya area) and is based on the sensitivity of passive microwave polarization ratios to ice thickness in the range of 0-20 cm (Willmes et al, 2010).…”
Section: Linkage Between Ice Area Flux and Summer Ice Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies from the south-eastern Laptev Sea already revealed unusually wide and late polynya openings in April 2007 (Willmes et al, 2011), which were not effective in the formation of brine-enriched bottom water (Bauch et al, 2010) usually observed with salinity of about 30 (Bauch et al, 2005). Further studies have to investigate which pattern will be more prominent in the future and how this may affect the Arctic Ocean halocline.…”
Section: Central Arctic Ocean F R / F Imentioning
confidence: 97%
“…Because of this decline in ice cover, large areas of the ocean especially on the shelves have been free of sea-ice for prolonged periods of time. Climatic changes may have an impact on the freshwater balance of the Arctic Ocean (Dickson et al, 2007;Rabe et al, 2011) and the change in sea-ice cover may specifically influence the occurrence of coastal polynyas and thus, the amount of sea-ice formed there (Willmes et al, 2011). Therefore, in order to further understand possible consequences and feedbacks of the current and future changes, it is of fundamental importance to get a more detailed understanding of the Arctic system and to identify sources of the Arctic Ocean halocline waters with respect to regions and processes of formation.…”
Section: Introductionmentioning
confidence: 99%